Istidraj in the Qur'an (Thematic Study of the Istidraj Verses in the Tafsir Mafatih Al-Ghaib by Fakhr Al-Din Al-Razi) - Mukarromah, Luluk; Ghufron, Achmad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
God gives man many favors, but man often abuses those pleasures on negative things, even to the point of forgetting God's commands in His shari'a. Often, we see people who disobey and ignore God's commands actually given smooth enjoyment and sustenance. They did not realize that the God-given favor was His wrath. This is what is called istidraj. This study aims to find out al-Razi’s interpretation of istidraj verses and al-Razi's interpretation analysis of istidraj verses in mafatih al-Ghaib's interpretation. Knowledge about istidraj is very important so that we as Muslims do not fall into istidraj behavior and can avoid things that lead to this behavior.